Convergence of p-series revisited with applications - Elom K. Abalo; Kokou Y. Abalo (International Journal of Mathematics and Mathematical Sciences)
We construct two adjacent sequences that converge to the sum of a given convergent p-series. In case of a divergent p-series, lower and upper bounds of the (kn)th partial sum are constructed. In either case, we extend the results obtained by Hansheng and Lu (2005) to any integer k≥2. Some numerical examples are given.